Ácido guanidinoacético, nucleotídeos e microminerais na alimentação de frangos de corte - Santos, Emanuelle Cristine dos (2020)
Due to the fact that Brazil is one of the largest poultry producers in the world, constantly requiring search for new solutions for their production, also knowing that the breast must meet the requirements of the market, considering that myopathies cause rejections to consumers and that studies on myopathy are not yet confirmed. Thus, the objective of this work was to evaluate the effect of supplementation of different minerals (selenium and chromium) and food additives (guanidinoacetic acid and nucleotides) on performance, blood parameters, carcass and cut yield, meat quality, proximate composition and incidence of pectoral myopathies. A total of 1500 broilers were used, distributed in a completely randomized design in a 4 x 3 factorial scheme, totaling 12 treatments and 5 replications per treatment. , (II) control diet supplemented with 0.25 mg kg-1 selenium (III) control diet supplemented with 0.50 mg kg-1 of chromium and (IV) control diet supplemented with 0.25 mg kg-1 of selenium and 0.50 mg kg-1 of chromium) and another factor was the supplementation of food additives: (I) without additive, (II) 600 mg kg-1 of acetic guanidinic acid - GAA (III) 1000 mg kg-1 of nucleotides. At 10, 28 and 42 days of age, broilers weight and feed intake were recorded for performance evaluation, and blood was collected from two birds per UE for assessment of blood parameters. For carcass yield, cuts and meat quality, two poultry were slaughtered per EU at 42 days of age. Subsequently, they were submitted to analysis of variance, and in case of difference P <0.05, the means were compared using the Tukey test. The results of the evaluation of the incidence of myopathies were submitted to the Kruskal Wallis test, in case of significant difference, the means were compared by the Bonferroni method at P <0.05. For blood biochemical parameters, interaction (P = 0.023) for creatinine kinase (CK) was observed at 42 days. The amount of crude protein in breast meat showed an interaction (P = 0.009) between food additives and minerals for birds slaughtered at 42 days. Cooking loss (PPC) showed an interaction (P = 0.028) at 42 days of age. Meat color at 42 days of age was observed interaction (P = 0.002) for the L * effect 24 hours post-mortem. Substances reactive to thiobarbituric acid (TBARS, mg MDA g-1) in broiler breast meat at 42 days of age showed an interaction (P = 0.002) between treatments for lipid oxidation at the 30th day of the storage period. There was an interaction (P = 0.006 and P = 0.037) between treatments for the wood chest score and stretch marks. In conclusion, supplementation of dietary nucleotides to diets did not affect performance, carcass and cut yield, blood profile and meat quality. Supplementation with GAA reduced the severity (7.8%) of WB, the incidence of severe (11.1%) and moderate (22.2%) WS scores at 42 days of age. The results associated with WB and WS suggest that GAA as a precursor to Creatine may have a potential benefit in reducing the severity of these myopathies.